Chad : Request for a Three-Year Arrangement under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2022)
The COVID-19 pandemic, the volatility in oil prices, heightened insecurity, and a looming food crisis due to climate change have severely stressed an already vulnerable Chadian economy. The two Rapid Credit Facility (RCF) disbursements in April and July 2020 allowed Chad to meet its immediate financing and urgent balance of payment needs in the early stages of the pandemic. The authorities have requested Fund assistance under the ECF to support their post-COVID recovery and their plan to reduce debt vulnerabilities through a combination of a debt workout and a multi-year fiscal consolidation program. However, due to the death of the president following a resurgence of fighting with rebel groups in April and the delayed delivery of donor support, the treasury situation has become extremely tight, threatening social stability.